Comparing the Patient‐Reported Physical Function Outcome Measures in a Real‐Life International Cohort of Patients With Psoriatic Arthritis. Issue 4 (13th March 2021) - Leung, Ying Ying; Orbai, Ana‐Maria; de Wit, Maarten; Balanescu, Andra; Dernis, Emmanuelle; Soubrier, Martin; Eder, Lihi; Smolen, Josef S.; Coates, Laura C.; Gossec, Laure; ,
Abstract : Objective: We evaluated the psychometric properties of 3 patient‐reported outcome measures to assess the physical function in psoriatic arthritis (PsA). Methods: Data were available for the Health Assessment Questionnaire disability index (HAQ DI), the 12‐item Short Form instrument physical component summary (SF‐12 PCS), and the Psoriatic Arthritis Impact of Disease instrument functional capacity score (PsAID‐FC). Data came from a longitudinal study in 14 countries of consecutive adults with definite PsA with ≥2 years of duration. The score distribution, construct validity, responsiveness, and thresholds of meaning of the patient‐reported outcome measures were evaluated. Results: At baseline, 414 subjects (52% male) were analyzed. The mean ± SD age was 52.4 ± 12.5 years and duration of illness was 10.9 ± 8.1 years. Ceiling effects were noted in 31% and 21% of patients for HAQ DI and PsAID‐FC, respectively; floor effects were minimal. All 3 patient‐reported outcome measures met a priori hypotheses for construct validity. After a median follow‐up of 4.1 (interquartile range 2.7) months in 350 patients, 27%, 54%, and 18% of patients reported themselves improved, not changed, and worsened, respectively. Change scores were statistically different for groups for worsening versus no‐change for all patient‐reported outcome measures. PsAID‐FC was more sensitive to change than the other 2 patient‐reported outcome measures. Comparing groups with worsening condition to no‐change, the standardized response mean square ratios were HAQ DI 29.9, SF‐12 PCS 16.7, and PsAID‐FC 40.1. Conclusion: HAQ DI, SF‐12 PCS, and PsAID‐FC are valid measures of physical function for PsA. PsAID‐FC, a single question, performed similarly to the other patient‐reported outcome measures and may be an additional option to measure PsA‐specific physical function.